PROSES KEMITRAAN ANTARA INDUSTRI KECIL DENGAN PENGRAJIN SHUTTLECOCK DI DESA SUMENGKO KECAMATAN SUKOMORO KABUPATEN NGANJUK - Siti Fatimah; Mustapit Mustapit (UNEJ e-Proceeding, 2018)
Sumengko Village is one of shuttlecock industry center in Sukomoro District Nganjuk Regency. Increased demand for shuttlecocks cannot be fulfilled by small industry, so that small industry form the partnership with shuttlecock craftsman especially the less-capitalized craftsman. Partnerships have boosted the economy of society dan reduced unemployment. This research was intended to know: (1) process of partnership, and (2) partnership between small industry with shuttlecock craftsman in Sumengko Village Sukomoro District Nganjuk Regency. The research area was determined by purposive method in Sumengko Village. The research used descriptive qualitative method. Determination of informant conducted by snowball and purposive sampling. The methods used in collecting data are interviews, observation, and documentation. Data analysis method used is Miles and Huberman model and Ian Dey approach. The result of the research showed that: (1) The process of partnership between small industry and shuttlecock craftsman occurs in five stages, identification of vision and mission, preparation, make agreement, socialization, and realization of agreement, (2) The partnership between small industry and shuttlecock craftsman has a good relationship because of commitment, mutual trust, awareness of weakness and strength, rule clarity, mutual sharing, risk and benefits, enthusiasm, good communication, interdependence, mutual benefit, transparency, complementarity, and encouragement.